"Dialogues" Khurram Sohail. An Analytical Study - Iqbal, Saima; Kullu, Parveen Akhtar; Mujeed, Ayesha (sourcecoder, 2024)
Khurram Sohail’s interviews like stories and characters have many meanings hidden in them. There are layers of meaning in them. A desert of words is a forest of state. There are mirrors of wishes and birds of prayers. The questions asked in the interviews, which seem to fly in his conversation, confirm that Khurram Sohail is well versed in the art of research and spontaneity. Along with an interest in poetry and fine arts, philosophy, psychology also has a keen eye for historical background and current affairs. They avoid repeating things, write their thoughts in a logical manner, have a keen eye on the past, present and future in the context of each topic. After reading this book, one feels the true dedication to Khurram Sohail’s work. The special feature of Khurram Sohail’s interviews is that he understands the depth and breadth of the world’s political, cultural and social issues, and while he adds to the reader’s knowledge, he also captures the emotions and feelings of his interviews .This article presents an analytical study of “Batoon ki piali main thandi chay” “Surmaia” “segha Baig” and “ Sazindhy”.